Financial markets and economic growth in Poland : simulations with an econometric model - Piotr Wdowiński (Center for Economic Studies and ifo Institute (CESifo), 2005)
In this paper we present simulations of economic performance of the Polish economy based on a quarterly econometric model. The model consists of 22 stochastic equations, which link the financial market with the real economy. The purpose of the research is to present effects of changes to domestic and foreign interest rates and the EUR/USD exchange rate on economic growth in Poland over the period Q2, 1993 – Q2, 2003.
Keywords: E6; G1; C5; C3; F1; 330; financial market; economic growth; econometric model; simulation; Poland; Wirtschaftswachstum; Finanzmarkt; Schätzung; Polen